Western Immunoblotting for the Diagnosis of Enterococcus faecalis and Streptococcus gallolyticus Infective Endocarditis - Arregle, Florent; Gouriet, Frédérique; Amphoux, Bernard; Edouard, Sophie; Chaudet, Hervé; Casalta, Jean-Paul; Habib, Gilbert; Fournier, Pierre-Edouard; Raoult, Didier (Frontiers in Cellular and Infection Microbiology, 2019)
Blood culture-negative endocarditis (BCNE) remains a diagnostic challenge. In our center, despite a systematic and exhaustive microbiological diagnostics strategy, 22% of patients with BCNE remain without an identified etiology. In an effort to determine the relevance of using Western blot (WB) for the etiological diagnosis of BCNE in patients with early antibiotic use, we developed specific assays for the major infective endocarditis (IE) causative agents, namely S. aureus, E. faecalis , S. anginosus and S. gallolyticus. Our technique was effective to identify the antigenic profiles of the 4 tested agents, but cross-reactions with S. aureus and S. anginosus antigens were frequent. A scoring method was developed for the diagnosis of E. faecalis and S. gallolyticus IE using the presence of reactivity to at least two antigenic bands for each bacterium and the positivity to at least one of the 300, 72 or 36 kDa proteic bands among for E. faecalis, and positivity for the two 75 and 97 kDa proteic bands for S. gallolyticus. We tested these diagnostic criteria in a prospective cohort of 363 patients with suspected IE. Immunoblotting for the diagnosis of E. faecalis IE showed a sensitivity of 100% and a specificity of 99%. The positive and negative predictive values were 73% and 100%, respectively. Regarding S. gallolyticus infection, immunoblot had a sensitivity of 100% and a specificity of 95%. However, the positive predictive value was 22% whereas the predictive negative value was 100%. Using WB, we identified a potential etiological agent in 4 of 14 BCNE cases with no identified pathogen. In conclusion, WB constitutes a promising and helpful method to diagnose E. faecalis or S. gallolyticus IE in patients with early antibiotic uptake and negative blood cultures.